2016
DOI: 10.1051/e3sconf/20160723005
|View full text |Cite
|
Sign up to set email alerts
|

Danish risk management plans of the EU Floods Directive

Abstract: Abstract. We evaluate the impact and effect of the EU Flood's Directive (2007/60/EC) in Denmark and the flood risk management plans that are the result of the national implementation. In a qualitative research approach, the flood risk management plans published by 22 Danish municipalities are reviewed and analyzed regarding main objectives and structural and non-structural mitigation measures. From the analyses conclusions are drawn on the non-structural risk management measures still to be improved to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Even with the EU Flood Directive being implemented in 2007, many Danish municipalities lack explicit objectives on how to go about accomplishing this goal [32]. In January 2018, Danish lawmakers agreed on regulating the Planning Act to prevent damage caused by flooding and erosion, providing municipalities with the legal framework to begin combating SLR.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the EU Flood Directive being implemented in 2007, many Danish municipalities lack explicit objectives on how to go about accomplishing this goal [32]. In January 2018, Danish lawmakers agreed on regulating the Planning Act to prevent damage caused by flooding and erosion, providing municipalities with the legal framework to begin combating SLR.…”
Section: Discussionmentioning
confidence: 99%
“…As each municipality in Denmark has to provide its own climate change adaptation plan by law since 2014 (Jensen et al, 2016), the legislative basis for having an appropriate plan can be ensured. In addition, the connected risk assessments to the EU Floods Directive (2007/60/EC) required ten risk areas in Denmark to prepare more concrete risk management plans in connection with flooding (Jebens et al, 2016). This has been updated in 2018, extending the old and adding new flood risk areas.…”
Section: Case Selectionmentioning
confidence: 99%
“…These zones can be assumed to have particular experience and knowledge of risk management planning for natural hazards, focused on flooding. Additionally, the classification through the EU Floods Directive (2007/60/EC) also suggested that the appointed areas are particularly vulnerable to natural hazards, so that the stakeholders have particular reason to care about the risk of compound events (Jebens et al, 2016). Moreover, the precondition that these municipalities were not otherwise interdependent nor close to each other should be met.…”
Section: Case Selectionmentioning
confidence: 99%
“…Even though Denmark has abundant groundwater resources, some regions are experiencing pressure on groundwater due to rising temperatures and evapotranspiration [39], and the need for irrigation systems might increase in the future. Therefore, the main concern of these changes on the groundwater table on the region are on the water supply impacts they will cause, from drinking water supply to irrigation issues, while flooding risks are seen as very local hazards that will be mainly caused by heavy precipitation, cloudbursts, and coastal floods from sea level rise [40].…”
Section: Study Areamentioning
confidence: 99%
“…This is especially relevant when considering that the water table rising closer to the surface would translate into a higher risk of flooding, especially in case of heavy precipitation events [29]. It is highly possible that the risk of flooding will be very local, and specific to certain events such as heavy storms events [40].…”
Section: Future Predictionsmentioning
confidence: 99%